8D.05: THE ROLE OF NEPRILYSIN IN ANGIOTENSIN 1-7 FORMATION IN THE KIDNEY. (June 2015) - Domenig, O.; Manzel, A.; Grobe, N.; Kaltenecker, C.; Kovarik, J.; Stegbauer, J.; Gurley, S.B.; Antlanger, M.; Elased, K.; Saemann, M.; Linker, R.; Poglitsch, M.
Abstract : Objective: Cardiovascular and renal pathology is frequently associated with a hyperactivated Renin-Angiotensin-System (RAS) and increased levels of its vasoconstrictive metabolite Angiotensin II. RAS blockade is a widely used therapeutic approach to treat hypertension and prevent hypertonic nephropathy. Due to a well-documented vasodilatory and renoprotective activity of Angiotensin 1–7 and its receptor Mas, the so-called alternative RAS axis reached the focus of therapeutic research. ACE2, a well-described Angiotensin 1–7 producing enzyme, is appreciated as the most important enzyme shifting the RAS towards the alternative RAS-axis. In this study, we aimed to investigate renal angiotensin metabolism and the enzymatic characterization of Angiotensin 1–7 formation pathways in murine and human kidneys. Design and method: We assayed murine kidney angiotensins in wildtype and ACE2 knockout mice by RAS-Fingerprint analysis. Moreover, we investigated the ex vivo metabolism of spiked Angiotensin I or Angiotensin II in presence and absence of selective inhibitors in kidney extracts by mass spectrometry. MALDI-Imaging was used to investigate renal location of angiotensin metabolism. Results: Renal Angiotensin 1–7 concentrations were unaffected by ACE2 deficiency, pointing to alternative enzymes contributing to the renal formation of this peptide. Metabolic analysis revealed a major role of Prolyl-Carboxypeptidase (PCP) in Angiotensin 1–7 formation in mice. We identified neprilysin (NEP) depended conversion of Angiotensin I to Angiotensin 1–7 to be the main pathway of Angiotensin 1–7 formation in murine kidneys, which was mainly located in the renal cortex, as confirmed by MALDI-Imaging. Further testing the potential relevance of these findings for antihypertensive and renoprotective therapy in humans, we analysed angiotensin metabolism in human living donor kidney biopsies. In contrast to mice, the Angiotensin II degrading activity of ACE2 directing the RAS to the alternative Angiotensin 1–7 axis is predominant compared to PCP. Conclusions: Our data show that in contrast to ACE2, NEP is an important activator of the alternative RAS in the murine and human kidney, which could lead to novel therapeutic strategies in hypertonic nephropathy and could explain molecular mechanisms of action of renoprotective drugs in use.